2003
DOI: 10.1017/s1355617703970068
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical functions in cognition: Toward a consensus

Abstract: SYNOPSISBehavioral neurologists and neuropsychologists have debated the role of the thalamus and basal ganglia in cognition and behavior for more than a century (e.g., Bucy, 1942;Marie, 1906;Penfield & Roberts, 1959;Wernicke, 1874). However, over these 100-plus years, there is little consensus regarding whether or how these structures contribute to cognition. Fortunately, recent research findings are rapidly changing this state of affairs. It is now obvious we will not understand how the brain controls complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…It is not known whether this finding represents something which will be confirmed by future studies of episodic memory after TBI, or whether it is unique to this experiment and the condition of word recognition. It should be noted, however, that there is evidence that the structures shown to be active in this portion of the experiment are important in language processing (see Crosson & Haaland, 2003, for a review) as well as other cognitive functions. Even if these subcortical structures are not specifically damaged after TBI (as suggested by Primus, et al, 1997), they are highly interconnected through white matter tracts known to be especially susceptible to injury via TBI (e.g., Whyte, Hart, Laborde, & Rosenthal, 2005), and other researchers (e.g., Little, et al, 2010), have found differences in cognitive functioning associated with damage to thalamic projection fibers.…”
Section: Discussionmentioning
confidence: 96%
“…It is not known whether this finding represents something which will be confirmed by future studies of episodic memory after TBI, or whether it is unique to this experiment and the condition of word recognition. It should be noted, however, that there is evidence that the structures shown to be active in this portion of the experiment are important in language processing (see Crosson & Haaland, 2003, for a review) as well as other cognitive functions. Even if these subcortical structures are not specifically damaged after TBI (as suggested by Primus, et al, 1997), they are highly interconnected through white matter tracts known to be especially susceptible to injury via TBI (e.g., Whyte, Hart, Laborde, & Rosenthal, 2005), and other researchers (e.g., Little, et al, 2010), have found differences in cognitive functioning associated with damage to thalamic projection fibers.…”
Section: Discussionmentioning
confidence: 96%
“…The healthy participants also showed a cluster of activation in the right thalamus. The precise role of the thalamus in language processing is not clear (e.g., Crosson and Haaland, 2003). However, a number of studies suggest that it is involved in semantic processing (Raymer et al, 1997; Kraut et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary cognitive neuroscience implicates the striatum in a cortical‐subcortical network that mediates cognitive functions, including executive function, working memory (Crosson and Halland 2003) and language (Copland 2003), with these functions often impaired after TBI. Specifically, DAergic and glutamatergic interactions within cortical‐basal ganglia loops critically impact motor and cognitive function (Canales et al .…”
Section: Discussionmentioning
confidence: 99%